A257 NEW ONSET ULCERATIVE COLITIS IN A PATIENT WITH KNOWN AUTOIMMUNE HEPATITIS TYPE 1. (26th February 2020) - Hasan, M; Gallinger, Z
Abstract: Background: Elevated transaminases can occur in up to 17 per cent of cases of Inflammatory Bowel Disease (IBD) 1, with many cases related to concurrent autoimmune conditions of the liver. Primary Sclerosing Cholangitis (PSC) is the most common autoimmune disease of the liver that is associated with IBD. Other causes of liver inflammation in patients with IBD can include Autoimmune Hepatitis (AIH). Aims: We aim to report a case of new onset ulcerative colitis in a patient with autoimmune hepatitis type 1 in the absence of concomitant PSC. Methods: Case report and review of literature. Results: A 25-year-old male with painless jaundice and was found to have Autoimmune hepatitis type 1 with typical morphological changes, positive Antinuclear antibodies and elevated IgG levels. Histopathological exam of the liver did not show any direct changes to the bile ducts to suggest PSC. The patient was started on steroids and Mycophenolate Mofetil (MMF) and developed new onset diarrhea. Colonoscopy was performed and both endoscopic and pathological findings were suggestive of likely inflammatory bowel disease, although drug induced colitis (MMF) could not be excluded. Conclusions: We conclude that there is a link between autoimmune hepatitis with IBD, in absence of concomitant PSC. Funding Agencies: None